2013
DOI: 10.5114/wiitm.2011.35794
|View full text |Cite
|
Sign up to set email alerts
|

Initial experience with implantation of novel dual layer flow-diverter device FRED.

Abstract: Flow-diverting stents can help treat complex and wide-necked cerebral aneurysms. The aim of the study was to evaluate initial experiences related to the safety and effectiveness of eight aneurysms treated with a new dual layer coverage designed flow-diverter device. In 2012 Fred flow-diverter devices were used to treat 8 unruptured wide neck (dome-neck ratio ≤ 1.5) and sidewall aneurysms in 6 patients. All aneurysms were located in the anterior circulation on the internal carotid artery (ICA). In 4 larger aneu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 22 publications
(20 reference statements)
0
20
0
Order By: Relevance
“…In the group of large aneurysms whose follow-up was available, only 6/8 (75 %) [20,25] were occluded at the last follow-up, while the occlusion rate of giant aneurysms was even lower (57 % or 4/7). Conversely, aneurysms located beyond the circle of Willis, as ACA [17,20], showed complete occlusion at the last followup, at 3, 6, and 12 months, respectively.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…In the group of large aneurysms whose follow-up was available, only 6/8 (75 %) [20,25] were occluded at the last follow-up, while the occlusion rate of giant aneurysms was even lower (57 % or 4/7). Conversely, aneurysms located beyond the circle of Willis, as ACA [17,20], showed complete occlusion at the last followup, at 3, 6, and 12 months, respectively.…”
Section: Discussionmentioning
confidence: 85%
“…Four recent studies [12,17,20,25] have reported the experience of treatment of cerebral aneurysms by FRED FDD. The data of these series and our own, including 103 patients with 107 aneurysms, are summarized in Table 4.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…It is characterized by a 2-layer structure consisting of high-porosity outer and low-porosity inner layers. [10][11][12] To introduce this product in Japan, a clinical trial involving four institutions in Japan has been conducted since 2013. In Toranomon Hospital, the trial was started after its protocol was approved by the Ethics Review Board, and is currently being conducted.…”
Section: Introductionmentioning
confidence: 99%